1979
DOI: 10.1021/ac50041a001
|View full text |Cite
|
Sign up to set email alerts
|

Application of macrocyclic compounds in chemical analysis

Abstract: Macrocyclic compounds are uncharged and contain a cavity in which a cation can be encapsuled. The complexes thus formed are of great analytical interest, but relatively few papers dealing with these compounds have been published in analytical journals as compared to hundreds of publications in a variety of nonanalytical journals.In the present review and discussion, we will often refer to the macrocyclic compounds as ligands and denote them by the symbol L, while a complex with a cation Cn+ is denoted by LCn+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(63 citation statements)
references
References 176 publications
0
63
0
Order By: Relevance
“…It can be found that the fixed-EQCM de tec tion sys tem ex hibited fairly low de tec tion lim its of 0.10-0. 13 16. Time and ion con cen tra tion ef fects on the frequency shifts of Ag + ions with the EQCM detec tion sys tem at an ap plied po ten tial of 0.3 V. the tra di tional QCM de tec tion sys tem.…”
Section: De Tec Tion Limit For Qcm For Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the fixed-EQCM de tec tion sys tem ex hibited fairly low de tec tion lim its of 0.10-0. 13 16. Time and ion con cen tra tion ef fects on the frequency shifts of Ag + ions with the EQCM detec tion sys tem at an ap plied po ten tial of 0.3 V. the tra di tional QCM de tec tion sys tem.…”
Section: De Tec Tion Limit For Qcm For Ionsmentioning
confidence: 99%
“…This se lec tiv ity or der was sim i lar to the se quence of the dis so ci a tion con stants (pKa) of these carboxylic ac ids. 24 This re sult may be at trib uted to the complexation 16 be tween the crown ether mol e cule and the dis so ci ated prod uct, H + ion of for mic acid and for ma tion of ion pair RCCO -H + -B15C5COC 17 H 35 (ad sor bent), which re sults in the fre quency shift of the quartz crys tal.…”
mentioning
confidence: 99%
“…These reviews cover topics as widely varied as synthesis [13], complexation chemistry [14], extraction [15] and transport behavior [5,16,17], analytical applications [18,19] and complexation with neutral guest molecules [20]. Only in a very limited number of these compilations [2,5,7,18,19] are proton-ionizable crown ethers identified as an important class of macrocyclic polyethers.…”
Section: T Osa and 1 L Atwood (Eds) Inclusion Aspects Of Membranmentioning
confidence: 99%
“…Macrocyclic compound is an important reference compound in chemistry studies such as complexation to metal due to existence electron donating atom in the ligand [8][9]. Some of macrocyclic derivatives have been reported showing great capability in antibacterial, anticancer and HIV treatment [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%